2021
DOI: 10.1021/acsami.0c21956
|View full text |Cite
|
Sign up to set email alerts
|

Facile Designed Manganese Oxide/Biochar for Efficient Salinity Gradient Energy Recovery in Concentration Flow Cells and Influences of Mono/Multivalent Ions

Abstract: Development of effective, environmentally friendly, facile large-scale processing, and low-cost materials is critical for renewable energy production. Here, MnO x /biochar composites were synthesized by a simple pyrolysis method and showed high performance for salinity gradient (SG) energy harvest in concentration flow cells (CFCs). The peak power density of CFCs with MnO x /biochar electrodes was up to 5.67 W m –2 (ave. = 0.91 W m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…1 c). More importantly, the feature at 1103 cm −1 demonstrates the presence of the conducting form of PANI on the surface of HPC, and the feature at approximately 511 cm −1 proves the existence of Mn-O on the MnO 2 /HPC composite surface ( Evans et al., 2019 ; Tan et al., 2021 ). The transmission electron microscopy (TEM) images of the MnO 2 /HPC and PANI/HPC clearly show that both MnO 2 and PANI were formed on the HPC surface, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…1 c). More importantly, the feature at 1103 cm −1 demonstrates the presence of the conducting form of PANI on the surface of HPC, and the feature at approximately 511 cm −1 proves the existence of Mn-O on the MnO 2 /HPC composite surface ( Evans et al., 2019 ; Tan et al., 2021 ). The transmission electron microscopy (TEM) images of the MnO 2 /HPC and PANI/HPC clearly show that both MnO 2 and PANI were formed on the HPC surface, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The high‐frequency semicircle represents the charge transfer resistance ( R ct ), and the low‐frequency region describes the ionic diffusion resistance ( σ ). [ 43 ] Compared to the LMO electrode ( R ct = 0.63 Ω, σ = 4.12 Ω), the LMO‐Al0.05 electrode ( R ct = 0.42 Ω, σ = 2.99 Ω) had a relative lower electrode resistance, implying that Al doping may facilitate Li + diffusion (Figures 2d and S3, Supporting Information). Previous studies have demonstrated that Al doping can enhance material conductivity and improve Li + diffusion behavior in LMO electrode.…”
Section: Resultsmentioning
confidence: 99%
“…6 Beyond its substantial potential, salinity gradient energy also holds a theoretical advantage in terms of relatively high volumetric power density. 7,8 Capacitive mixing (CapMix) represents one of the popular technologies to harvest blue energy. 9 The CapMix method is based on capacitive double-layer expansion (CDLE), which involves two electrodes submerged alternatively in the stream of seawater (SW) or freshwater (FW), forming a capacitor.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity gradient energy, generated by mixing two solutions of different salt concentrations, is regarded as a promising source of renewable energy, , which can boost an estimated global power potential ranging from 1.40 to 2.60 terawatt . Beyond its substantial potential, salinity gradient energy also holds a theoretical advantage in terms of relatively high volumetric power density. , …”
Section: Introductionmentioning
confidence: 99%